Utilisation of early childhood education and care services in a nationally representative sample of Australian children: A focus on disadvantage - Wong, Sandie; Harrison, Linda; Rivalland, Corine; Whiteford, Chrystal (My University, 2014)
Attendance in high-quality early childhood education and care (ECEC) has been shown to have a positive influence on young children’s development and life chances, especially for those children from disadvantaged backgrounds. A number of government policies are in place, both internationally and in Australia, to support these children’s use of ECEC services. But to what extent do Australia’s most vulnerable children use ECEC? Drawing on data from Growing up in Australia: The longitudinal study of Australian children (LSAC) this paper demonstrates that children from a range of disadvantaged groups do use ECEC. However, based on more in-depth analyses using a Disadvantage Index, the paper also shows that children with multiple indicators of disadvantage were more likely to be in exclusive parental care, less likely to be using preschool and using fewer hours of care than their peers. These findings suggest that there may be barriers to ECEC utilisation for children and families for whom ECEC potentially has the most benefit.
Keywords: Child Care; Disadvantage; Child Development; Children -- Early childhood; Childhood and child development; Children; Child Care; Disadvantage; Child Development; Early childhood; Childhood and child development